Ischaemum mistryi (Poaceae: Andropogoneae): A new remarkable species from Sub-Tropical Evergreen Forest, India - Landge, Shahid Nawaz; Shinde, Rajendra D. (Phytotaxa, 2021)
Ischaemum mistryi, a new species from the Sub-Tropical evergreen forest of Tilari Ghat, Maharashtra, India, is described and illustrated. This grass is unique with its leaves drooping, mostly congregated near the base, basal sheath villous, culms compressed at the base, lower glume of the sessile spikelet linear-lanceolate to oblongish tapering and slightly curled upwards, without a sub-apical ridge, nodules absent (if present 2–4 obscure) on its keels, and upper lemma of sessile spikelet bi-partite. Morphologically it is somewhat similar to I. mangaluricum, I. travancorense and I. barbatum. We provided a table of its detailed comparison with close species as mentioned above. According to IUCN Red List Categories and Criteria, we have assessed this new species as Critically Endangered (CR). The photo plates and illustration of the grass are given to facilitate its proper identification. A short discussion is also provided at the end.